The evaluation of dietary application of conjugated linoleic acid on performance, egg quality, blood parameters, antioxidant capacity and egg yolk cholesterol parameters in layer quails - GÜMÜȘ, E.; SEVIM, B.; CUFADAR, Y. (Journal of the Hellenic Veterinary Medical Society, 2021)
Conjugated linoleic acid (CLA) is a poly unsaturated fatty acid (FA) which is accepted as favorable for human health. The aim of this study is to ascertain the effects of CLA on performance, egg quality traits, egg yolk and albumin pH levels, blood serum biochemical parameters, egg yolk cholesterol content and blood antioxidant capacity in layer quails. 96 7-weeks-old female Japanese quails divided to 4 groups with 6 subgroups and the groups fed with basal diet supplied with 0 g/kg, 10 g/kg, 20 g/kg and 30 g/kg CLA respectively for 8 weeks. Our results indicated that CLA supplementation did not statistically affect performance, egg quality traits, egg pH levels, total antioxidant capacity in blood serum and yolk cholesterol content. Although dietary CLA did not significantly differ between groups for blood serum total protein, glycose, total cholesterol, triglyceride and high-density lipoprotein; lipoprotein lipase levels were significantly decreased in CLA supplemented groups (p<0.05). In summary, our results have shown dietary CLA supplementation might affect lipid metabolism and enzyme activity in female Japanese quails.